2017
DOI: 10.1111/jicd.12292
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of CD4 count with cariogenic oral flora indicators and dental caries in HIV‐seropositive children undergoing antiretroviral therapy in Mangaluru, South India

Abstract: No statistically-significant correlation was found between CD4 count and cariogenic oral flora indicators in HIV-positive patients. The presence of a minimum number of restored teeth compared to decayed teeth suggests a lack of dental care being given to HIV-positive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“… 35 However, one study had pointed out that there was no statistical significance between the CD4+ cell count and caries in HIV-positive children treated with ART in Mangaluru, India. 36 In this study, the prevalence of caries remained very high in both groups, which was 82.75% in the adolescence group and 84.8% in the young adult group. Participants in this study had received HAART for a long period, and achieved good therapeutic effect.…”
Section: Discussionmentioning
confidence: 46%
“… 35 However, one study had pointed out that there was no statistical significance between the CD4+ cell count and caries in HIV-positive children treated with ART in Mangaluru, India. 36 In this study, the prevalence of caries remained very high in both groups, which was 82.75% in the adolescence group and 84.8% in the young adult group. Participants in this study had received HAART for a long period, and achieved good therapeutic effect.…”
Section: Discussionmentioning
confidence: 46%
“…Although PHIV youth in this study had higher decay rates and caries scores than their uninfected counterparts, no correlation was found between the amount of tooth decay, current/nadir CD4 cell counts, or viral load after adjustments for similar covariates in the PHEU group. Similarly, Muraleedharan et al 17 in South India reported no correlation between CD4 count and dmft among a small cohort of 35 children (mean age 10.97 SD 4.21).…”
Section: Discussionmentioning
confidence: 88%
“…observed that the caries experience increased in children undergoing ART increased to 86% 13 whereas a study done by Muraleedharan et al. showed a decreased incidence of dental caries in children with ART 14 and Ponnam et al. found no significant effect of ART on caries prevalence 15…”
Section: Introductionmentioning
confidence: 92%
“…9 The evidence regarding the association between dental caries, gingival health and HAART is mixed. Meless et al observed that the caries experience increased in children undergoing ART increased to 86% 13 whereas a study done by Muraleedharan et al showed a decreased incidence of dental caries in children with ART 14 and Ponnam et al found no significant effect of ART on caries prevalence. 15 Since, there is insufficient data regarding the prevalence of caries and gingival status in CLHAs and ALHAs in those undergoing HAART with HAART naïve (receiving no ART) CLHAs and ALHAs, this study was devised to assess dental plaque and dental caries in CLHAs and ALHAs in those undergoing HAART with HAART naïve CLHAs and ALHAs.…”
Section: Introductionmentioning
confidence: 97%